2012
DOI: 10.1126/science.1219088
|View full text |Cite
|
Sign up to set email alerts
|

Color and Albedo Heterogeneity of Vesta from Dawn

Abstract: Multispectral images (0.44 to 0.98 μm) of asteroid (4) Vesta obtained by the Dawn Framing Cameras reveal global color variations that uncover and help understand the north-south hemispherical dichotomy. The signature of deep lithologies excavated during the formation of the Rheasilvia basin on the south pole has been preserved on the surface. Color variations (band depth, spectral slope, and eucrite-diogenite abundance) clearly correlate with distinct compositional units. Vesta displays the greatest variation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
240
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 167 publications
(261 citation statements)
references
References 34 publications
(12 reference statements)
21
240
0
Order By: Relevance
“…Howardites and eucrites along with diogenites (HED meteorites) have been linked to asteroid (4) Vesta, on the basis of their spectral and mineralogical similarities derived from groundbased observations (e.g., McCord et al, 1970;Consolmagno and Drake, 1977;Gaffey, 1997;. This idea has been supported by recent spacecraft spectroscopic observations obtained by Dawn (e.g., Reddy et al, 2012b;De Sanctis et al, 2012), that shows Vesta as the most likely parent body of these meteorites. The Vesta asteroid family extends from the ν 6 secular resonance to the 3:1 mean motion resonance with Jupiter, providing a viable route for the delivery of these objects to the near-Earth space (Wisdom, 1985;Bottke et al, 2002).…”
Section: Discussionsupporting
confidence: 59%
“…Howardites and eucrites along with diogenites (HED meteorites) have been linked to asteroid (4) Vesta, on the basis of their spectral and mineralogical similarities derived from groundbased observations (e.g., McCord et al, 1970;Consolmagno and Drake, 1977;Gaffey, 1997;. This idea has been supported by recent spacecraft spectroscopic observations obtained by Dawn (e.g., Reddy et al, 2012b;De Sanctis et al, 2012), that shows Vesta as the most likely parent body of these meteorites. The Vesta asteroid family extends from the ν 6 secular resonance to the 3:1 mean motion resonance with Jupiter, providing a viable route for the delivery of these objects to the near-Earth space (Wisdom, 1985;Bottke et al, 2002).…”
Section: Discussionsupporting
confidence: 59%
“…In the Clementine color ratio map the lobe shows comparable colors to the Rheasilvia ejecta (ranging from cyan via green to yellowish colors) within and around Vesta's south pole. The bright green/yellow indicates a deeper 1-lm absorption band and is consistent with terrains interpreted to be diogenite-rich howardite, such as in the Rheasilvia basin (Reddy et al, 2012a). This compositionally different material is also evident in the Dawn GRaND data which shows an eastern low-iron lobe extending northward from the Rheasilvia basin .…”
Section: Rheasilvia Ejectasupporting
confidence: 55%
“…This striking spectral feature appears as a swath of bright material in the FC clear filter images. Reddy et al (2012a) suggested it to be a thin mantle of material probably ejected during the Rheasilvia impact event. Using the spatially higher resolved LAMO data, the lobe region appears to have a smoother texture than typical vestan terrains outside the Rheasilvia basin, and is crosscut in some parts by numerous small grooves oriented approximately in the north-south direction.…”
Section: Rheasilvia Ejectamentioning
confidence: 99%
See 2 more Smart Citations